ANALISIS PERBEDAAN E-MARKETING MIX PADA TOKO ONLINE (Studi Pada Shopee dan Tokopedia) - Indah Yuni (2021)
This study aims to analyze and find out the differences between products, prices, distribution, promotions, service personnel, processes, and physical evidence on Shopee and Tokopedia. This research method is descriptive quantitative with 100 respondents of online shop consumers Shopee and Tokopedia scattered in South Jakarta. The data analysis technique was taken through a questionnaire with descriptive data analysis techniques, then the validity and reliability tests used the Statistical Package for the Social Sciences (SPSS) version 22.00 and hypothesis testing using the chi square. The results showed that (1) There were no product differences between the Shopee and Tokopedia online stores (2) There were differences in prices at the Shopee and Tokopedia online stores (3) There were no differences in distribution at the Shopee and Tokopedia online stores (4) There were differences in promotions at the shop Online Shopee and Tokopedia (5) There are no differences in service personnel at the Shopee and Tokopedia online stores (6) There are differences in the process for the Shopee and Tokopedia online stores (7) There are differences in physical evidence in the Shopee and Tokopedia online stores.